An Impact of Blended Learning Techniques At Educational Institutions In Chennai City - M.Radhikaashree,; K.Vimala,; S.Jayalakshmi, (International Journal of Psychosocial Rehabilitation, 2020)
This paper examines the efficiency of a blended learning setting through evaluating the association between student characteristics/background, design features and learning outcomes. It is intended at defining the substantial forecasters of blended learning effectiveness taking student characteristics/background and design features as independent variables and learning outcomes as dependent variables. A survey was administered to 248 respondents to gather data on student characteristics/background, design features and learning outcomes. The final semester assessment results were used as a measure for performance as an outcome. We applied the online self-regulatory learning questionnaire for data on learner self-regulation, the inherent motivation inventory for data on intrinsic motivation and other self-developed instruments for measuring the other constructs. Multiple regression analysis results showed that blended learning design features (technology quality, online tools and face-to-face support) and student characteristics (attitudes and self-regulation) predicted student satisfaction as an outcome. The results specify that some of the student characteristics/backgrounds and design features are significant predictors for student learning outcomes in blended learning.